2014
DOI: 10.1158/0008-5472.can-14-0923
|View full text |Cite
|
Sign up to set email alerts
|

Transient SNAIL1 Expression Is Necessary for Metastatic Competence in Breast Cancer

Abstract: SNAIL1 has been suggested to regulate breast cancer metastasis based on analyses of human breast tumor transcriptomes and experiments using cancer cell lines and xenografts. However, in vivo genetic experimental support for a role for SNAIL1 in breast cancer metastasis that develops in an immunocompetent tumor microenvironment has not been determined. To address this question, we created a genetic SNAIL1 model by coupling an endogenous SNAIL1 reporter with an inducible SNAIL1 transgene. Using multiple genetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
187
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(205 citation statements)
references
References 42 publications
(65 reference statements)
8
187
0
3
Order By: Relevance
“…This finding supports the notion that EMT is required for early seeding of metastasis, while MET is essential for metastatic outgrowth (Tsai et al 2012). Indeed, other studies have shown that an extreme EMT can lock cancer cells into a terminally differentiated state, depriving them of stem cell-like properties and cell plasticity and reducing tumor growth (Tran et al 2011(Tran et al , 2014Celia-Terrassa et al 2012).…”
Section: Epithelial-mesenchymal Plasticity and The Acquisition Of Stesupporting
confidence: 81%
“…This finding supports the notion that EMT is required for early seeding of metastasis, while MET is essential for metastatic outgrowth (Tsai et al 2012). Indeed, other studies have shown that an extreme EMT can lock cancer cells into a terminally differentiated state, depriving them of stem cell-like properties and cell plasticity and reducing tumor growth (Tran et al 2011(Tran et al , 2014Celia-Terrassa et al 2012).…”
Section: Epithelial-mesenchymal Plasticity and The Acquisition Of Stesupporting
confidence: 81%
“…tumor fibrosis) that affect tumor progression, invasion, metastasis and response to therapy, despite the continued presence of TWIST1. In sum, the TWIST1 data, our SNAIL1 data herein, and the SNAIL1 data from Stanisavljevic et al (2015) suggest that the primary role for TWIST1 in breast tumorigenesis could be in the tumor cell, whereas SNAIL1 function might be most important in CAFs, although genetic data also supports a role for SNAIL1 in tumor cells (Moody et al, 2005;Tran et al, 2014;Ye et al, 2015).…”
Section: Discussionmentioning
confidence: 55%
“…8E). SNAIL1 already has well described functions in tumor cells, where it can influence tumor-initiating cells and the invasion and metastasis of tumor cells (Ye et al, 2015;Moody et al, 2005;Tran et al, 2014). Less appreciated, perhaps, is the importance of SNAIL1 in mesenchymal cells (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…PTK6 specifically regulates the expression of SNAIL, and not other transcriptional repressors. SNAIL has been linked to generation of cancer stem cell properties (41), drug resistance (37), cancer recurrence and metastasis, all contributors to poor prognosis for patients (16,42). Although SNAIL is often transcriptionally regulated by EMT-inducing stimuli, here we show that PTK6 regulates the proteasome-dependent degradation of SNAIL protein.…”
Section: Discussionmentioning
confidence: 59%